Application of residential and public building dynamic characteristic assessment for diagnostics and monitoring of their technical condition - KHOKHLIN, Denis; MILITSKYI, Kostiantyn (Ways to Improve Construction Efficiency, 2025)
A significant number of studies of dynamic characteristics for different types of buildings and their structures in different states have been reviewed. It is noted that the allocation of specific generally applicable values of the oscillation periods (frequencies), which would allow to unambiguously characterizing the state of a structural system of a certain type, is problematic, because the dynamic characteristics depend on too many factors. At the same time, the use of averaged results of a sufficiently large group of different formulas of oscillation period experimental dependences on the main parameters of the structure can provide a fairly accurate value of the building oscillation expected period. It is also important to assess the impact of possible changes in the mass of the structure. It was determined that for residential and public buildings, the impact of a possible change in mass during operation on the frequency of natural oscillations can be estimated at approximately 5%. In the case of measuring the basic (starting) natural oscillation frequency of a completed but not commissioned building, a correction factor of 0.95 should be applied for comparison with subsequent measurements already during operation. It is noted that measurements of horizontal vibration characteristics are indicative and sensitive, first of all, to the state of vertical load-bearing structures, the rigidity of which most affects the period of such vibrations. Measurements of the characteristics of natural vibrations in horizontal directions will be most effective for assessing changes in the state of structures with a rigid structural system and frame structure without vertical ties, as well as the parameters of vertical vibrations of large-span floor and roof structures. According to the studies considered, the reduction in the vibration frequency of rigid stone (as a rule) residential and public buildings, significantly damaged by deformations of the foundation or earthquake (including up to an emergency state) was approximately 0.57…0.89, depending, first of all, on the building height and the damage degree. Based on experimental data, tables of approximate values of permissible reduction coefficients of the initial (relative to the beginning of operation) natural vibration frequency of public and residential buildings with a rigid structural system for technical condition categories and for similar buildings with a reinforced concrete flexible structural system are proposed. Further measures for the operation of the building are proposed based on the assessment of the technical condition category based on the results of measuring the building natural vibration frequencies. The development of methods for assessing the dynamic characteristics of buildings for diagnosing the technical condition of structures damaged by off-design influences, including the improvement of organizational and methodological tools for inspection with the aim of increasing the efficiency of recovering damaged objects, is proposed and considered.